Classes de aperfeiçoamento : ensaio da escola ativa no ensino primário em Sergipe (1932-1933) - Fontes, Juliana Santos (2018)
In this study, I sought to investigate the dissemination process of teaching Active, through the implementation of Improvement Classes, installed in school groups and in isolated schools in the State of Sergipe, in 1932 and 1933. In the Classes of Improvement were developed the centers of interest, created by Decroly and adopted in the Regulation of 1931. Aligned with Cultural History, the research was based on the concept of school culture, defended by Julia (2001), as the guiding principle for an analysis of the set of teachers practices that incorporate in the Classes in Sergipe. In addition, discussed the pedagogical guidelines through the work of Moura (1931), carried out by teaching inspectors. In the methodology used, of a descriptive historical nature, I searched in documentary sources, such as terms of visit of the inspectors of education, information of the school directors, primary education program, Regulation of February 3, 1931 and notes of the Official Gazette of this research, among other sources, the data needed to answer the research question: how did occured the process of dissemination of Active teaching through the implementation of the Improvement Classes installed in school groups and in isolated schools in the State of Sergipe in the years 1932 and 1933? I noticed that the Classes of Improvement had their proposal presented by Professor José Augusto da Rocha Lima, after a trip to the State of São Paulo in 1931 and were implemented in 32 Classes, in the period of 1932 and 1933, in the capital and in the interior of Sergipe. I also verified that the teachers' choices to direct the Class in the school groups, for the most part, had as criterion the demonstration of “competence” in the development of the method.The purpose of the Improvement Classes was fulfilled insofar as it disseminated the practice of the Intuitive Analytical Asset method with the use of Decroly centers of interest, which can be certified in the practices of teachers in the years 1933 and 1934.